Le rôle du numérique dans la redéfinition des communs urbains - Hervé Le Crosnier; Philippe Vidal (Netcom)
Before introducing urban commons, we provide a recall of majors approaches of the theory of the commons, and its differences between diverses local and cultural histories. We show how important are the commons for a sustainable and resilient city and for participative urbanism. Then we discuss the way digital equipment can lead to the conception of the city as a plateform, pointing limits of the service city and of new utopias brought to town by digital giants. Then we look how the commons and commoners can use the digital infrastructure around three subjects: how the digital helps coordinating actions and ideas of the commons; how it gives commonners the ability to show the urban commons, mostly through participative maps; and the importance of open data. We conclude on the concept of public-commons partnerships and the emergence of the new municipalism.